Face the music a life exposed - Stanley, Paul 1952- (Harper One, 2014)
The co-founder and lead singer of the rock band Kiss discusses his childhood, the drama of his life on and off the stage, his personal relationships, and the turbulent dynamics with his bandmates over the past four decades